Risk Management, Corporate Governance and Financial Performance of Sharia Commercial Banks - Ratna Sari; Aji Binawan Putra (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
Financial performance is an organization that can be used to describe the success of an organization, both in good and bad times. Due to the high complexity and risks associated with banking institutions, a bank's financial performance can be improved by developing an effective risk management strategy through good corporate governance. This study uses quantitative. This study aims to determine the effect of risk management on financial performance by using NPF and FDR to measure financing risk, BOPO to measure operational risk, NOM to measure capital adequacy, and the impact of GCG by using the size of the Board of Independent Commissioners, Directors. Data analysis uses Partial Least Square Software, namely the SmartPLS version 3 program to measure risk management of a company's financial performance. The study results show that risk management, as measured by NPF, BOPO, and CAR ratios, significantly positively affects financial performance in Islamic Commercial Banks. GCG has not been able to moderate management risk on financial performance. The risk management variable significantly impacts financial performance, so it is essential for sustainable financial performance improvement. The GCG variable has a negligible but not significant effect on financial results. It indicates that the GCG effort variable to convey the relationship between risk management and financial performance is unsuccessful.